Pengaruh Kualitas Layanan Digital Banking Terhadap Kepuasan Nasabah Pada Bank Syariah Indonesia Di Kabupaten Subang - Syifa Nurlatifah; Juhadi Juhadi; fenny Damayanti Rusmana (CV. ULIL ALBAB CORP, 2024)
Service quality is one of the factors of consumer satisfaction, so service quality is very important for the business world and organizations. Customer satisfaction with banking services brings long-term benefits to the bank and provides a competitive advantage for the bank itself compared to other banks. If customers are consistently satisfied with their bank's services, they are less likely to switch to another service provider or bank. This way, customers are more likely to reuse the service and promote it to others. The aim of this research is to determine